Studies on the Development of Mixed Fruit Marmalade (Journal of Environmental Science and Natural Resources, 2013)
This study reports on processing of mixed fruit marmalades from malta, mango and pineapple juices at different ratios. Sensory attributes and storage studies of the mixed fruit marmalades were also evaluated. The fresh and fully mature fruits were used for this experiment. Chemical characteristics such as moisture, ash, acidity, pH, vitamin C, sugar and total soluble solids (TSS) of fruit juices and mixed fruit marmalades were determined. Variations in chemical constituents were observed among the juice and marmalade samples. S1 sample was found best of all samples with respect to chemical composition. The analysis of chemical composition of S1 sample (malta juice: mango juice: pine-apple juice=2:1:1) was found as: moisture 27.71%, ash 0.16%, TSS 67.5%, total sugar 66.2%, acidity 0.90% and pH 2.8. On the basis of sensory evaluation the S1 sample was the most acceptable among others in terms of color, flavor, texture and overall acceptability. Storage study was conducted on the mixed fruit marmalades for six months at room temperature (23-30°C) and relative humidity 80 to 85%. It was observed that TSS, pH and acidity of mixed fruit marmalades did not show any remarkable changes. Color and flavor were acceptable throughout six months of storage period. After six month of storage period small amount of mould and bacterial attack was observed in marmalade samples. The microbial count was low due to high acidity and proper storage of the samples. The microbial contamination was very low in sample S1 than other samples due to its highest acidity.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14836 J. Environ. Sci. & Natural Resources, 5(2): 315-322 2012